Pengembangan Pariwisata Berbasis Masyarakat - Suta, Putu Wira Parama; Mahagangga, I Gusti Agung Oka (JURNAL DESTINASI PARIWISATA; Vol 5 No 1 (2017): VOL 5, NO 1 (2017): (JANUARY - JUNE) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2017.v05.i01.p26, 2018)
Tourism development should involve the local community as one of  strakeholders interest in its management. Therefore local communities also have the right to be able to taste the economic benefits equitably. This study aims to determine the participation of local communities in the management in Ekowisata Kampoeng Kepiting Tuban, Bali. This research is important because local community participation in ecotourism can determine sustainable development The research methodology used in this study is a qualitative research, with qualitative observation, semi-structured interviews, and documents qualitative as well as using the concept of a tourist attraction, management and public participation theory to analyze the problems in the field. The results show management in Ekowisata Kampoeng Kepiting is organized by Fishermen Group Wanasari Tuban, Bali and the employees who work not only from members of the fishermen but also come from family members of fishermen. Local community participation in the management is classified into spontaneous participation.   Keywords : Community Participation, Tourism Management, Ekowisata Kampoeng Kepiting